Investor Response to Management Decisions: A Research-Based Analysis of Actions and Effects. - Linn, Scott C.; Altman, Richard M. (Journal of Finance, 1993)
Preface Introduction Investing Decisions: Changes in Organizational Structure Investing Decisions: Changes in Ownership Structure Financing Decisions and Capital Structure Financial Policy Operating Decisions: Earnings and Forecasts The Market for Corporate Control Defense Tactics in the Market for Corporate Control Management Compensation and the Managerial Labor Market Management Response to Investor Decisions Bibliography Index